Beach volleyball performance benchmarks in men`s high level - Giatsis, G. (Journal of Human Sport & Exercise, 2023)
The aim of this study was to explore the set and technical indicators between winning and losing men`s teams in the 2022 beach volleyball World Championship, depending on the set of the matches to 21- (S21) and 15-points (S15). A total of 250 sets and 9,096 points were analysed from the men`s 2022 World Championship. Discriminant function analysis determined which skill(s) contributed significantly to winning a set in S21 and S15. This study showed that the teams that won S21 and S15 had better performance in all scoring skills (serve, attack, block, opponent errors), attack kill percent and attack and serve efficiencies compared to their opponents. The attack opponent errors points and attack kill percent, were the main predictors of a team`s success of set and technical indicators respectively. In conclusion, the results of the men's teams at the highest level of beach volleyball, show that attack kill percent is not the only technical indicator that increases the probability of winning a set, since attack opponent errors per set points contribute equally significantly. Furthermore, teams should reduce the number of attack errors despite the high level of blocking to increase the probability of winning a set.